2018
DOI: 10.1038/s41598-017-18522-4
|View full text |Cite
|
Sign up to set email alerts
|

A Mosquito Inspired Strategy to Implant Microprobes into the Brain

Abstract: Mosquitos are among the deadliest insects on the planet due to their ability to transmit diseases like malaria through their bite. In order to bite, a mosquito must insert a set of micro-sized needles through the skin to reach vascular structures. The mosquito uses a combination of mechanisms including an insertion guide to enable it to bite and feed off of larger animals. Here, we report on a biomimetic strategy inspired by the mosquito insertion guide to enable the implantation of intracortical microelectrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 67 publications
0
67
0
Order By: Relevance
“…Force and tissue compression are important metrics to gauge neural tissue damage, but a single unit count weeks after implant is required to fully demonstrate a neural recording technology for chronic use. Recently, promising strategies for insertion of flexible polymer devices through rat dura have been demonstrated (Shoffstall et al, 2018, Zhao et al, 2019, but such methods have not yet reported chronic, single-unit recordings in freely behaving animals. Here, we evaluated our single unit count at 95 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Force and tissue compression are important metrics to gauge neural tissue damage, but a single unit count weeks after implant is required to fully demonstrate a neural recording technology for chronic use. Recently, promising strategies for insertion of flexible polymer devices through rat dura have been demonstrated (Shoffstall et al, 2018, Zhao et al, 2019, but such methods have not yet reported chronic, single-unit recordings in freely behaving animals. Here, we evaluated our single unit count at 95 days.…”
Section: Discussionmentioning
confidence: 99%
“…Another complementary insertion strategy uses an insertion guide, as recently demonstrated for insertion of SMP devices through rat dura (Shoffstall et al, 2018). Inspired by the labium that guides the proboscis of the female mosquito, a guide at the insertion site increases the critical buckling load of the inserted device itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there has been some progress in the medically focused biomimetics. Bio‐inspired products intended for medical application are being developed including tenacious biological glues with anti‐proliferative, anti‐inflammatory and anti‐microbial activity based on sticky proteins (natures glue) secreted by the bivalve mussel species microprobes for brain surgery based on mosquito skin penetration , the red sweat of the hippopotamus that have antibiotic and sunscreen activity , and development of anti‐microbial surfaces modelled after the diamond‐like architecture of shark skin .…”
Section: The Zoobiquity Concept – Medical Doctors Can Learn From Vetementioning
confidence: 99%